Економічне стратегування та заходи щодо підвищення ефективності інноваційно-проєктної діяльності позашкільних мистецьких освітніх закладів - Пасечник, І.В. (Вісник економічної науки України, 2024)
В роботі запропоновано стратегічний підхід до підвищення ефективності інноваційно-проєктної діяльності в позашкільних мистецьких освітніх закладах України. В умовах сучасної глобалізації і мінливих вимог суспільства до якості освіти, ці заклади відіграють важливу роль у розвитку творчих здібностей молоді та їх естетичної освіченості. Основний фокус дослідження приділяється аналізу існуючих викликів та можливостей, які можуть бути використані для формування ефективних стратегій і практик.
Дослідження включає кілька ключових аспектів: розробку інноваційної стратегії для інтеграції новітніх технологій у навчальний процес, методи підвищення професійної компетенції викладачів, а також стратегія для розширення міжнародного співробітництва та партнерства. Автори пропонують комплексний план дій, який включає в себе впровадження інтерактивних та студентоцентричних методів навчання, інтеграцію цифрового мистецтва та віртуальної реальності, та акцент на міждисциплінарних проєктах.
Крім того, звертаємо увагу на необхідності економічної ефективності і фінансової стабільності інноваційних проєктів, висвітлюючи стратегії залучення додаткових ресурсів та оптимізації витрат через впровадження енергоефективних технологій та автоматизації процесів. Рекомендації також включають розробку нових платних програм, комерціалізацію продуктів діяльності закладів, а також стратегії для ефективного управління ризиками.
Завершується дослідження висновками, які підкреслюють значення інноваційно-проєктної діяльності для всебічного розвитку особистості учнів, підготовки їх до активної участі в культурному та професійному житті, а також необхідність постійного вдосконалення освітніх програм відповідно до сучасних вимог і технологічних досягнень. The article examines the state policy of supporting innovative processes in the market of artistic educational services in the context of economic interaction. The introduction defines the problem, emphasizing the importance of innovation as a key factor in economic development and the role of state support in realizing the potential of art education services. Recent research is analyzed, highlighting the need for continued research to identify effective strategies and policies.
The article highlights the types and instruments of state regulation of innovative activities in the field of extracurricular music education, including legislative, financial, institutional regulation and tax benefits. Additional aspects are considered, such as monitoring and evaluation of innovations, integration with international standards and personnel training.
Particular attention is paid to economic interaction, which includes stimulation of research and development, support of innovative startups and enterprises, infrastructure development and international cooperation. The benefits of economic interaction are discussed, including economic growth, social progress and increased competitiveness at the international level.
The conceptual scheme of the mechanism of the state policy of supporting innovative processes in the market of artistic educational services is presented, which includes types of regulation, instruments of state regulation, additional aspects and directions, measures and results of the implementation of the state policy of supporting innovative processes in out-of-school musical education institutions on the basis of economic interaction. This approach to the mechanism of public policy, which supports innovative activities in the sector of art education, taking into account economic aspects, provides an opportunity to develop and implement effective policies and strategies at the state level in an organized manner. Such a structured methodology allows taking into account all important elements and ensuring the optimal use of resources aimed at achieving defined strategic goals in the field of art education.
The findings highlight the importance of a comprehensive approach to supporting innovation in art education, where public policy plays a key role in stimulating the development and implementation of innovative practices at all levels.